The effect of melatonin treatment on doxorubicin-induced skeletal muscle atrophy within a cancer model - Isaacs, Ashwin Wayne (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.